Frequencies of feet feathering and comb type genes in the nigerian local chicken - C. O. N., Ikeobi; M. O., Ozoje; O. A., Adebambo; J. A., Adenowo (Universiti Putra Malaysia Press, 2001)
Incidence of feet feathering condition, different comb types and the relative frequencies of the genes affecting these conditions were studied in 2030 local chickens. 14.78% of the local chicken surveyed had feathered feet, while 85.22% had non feathered feet. The single comb type was the commonest of the comb type observed in the chickens surveyed. 94.73% of the chickens had single comb, while 3.20% and 2.07% had rose and pea combs respectively. The estimated gene frequency for fish allele affecting feet feathering in the breed was 0.08, while its recessive allele, fih an estimated frequency of O. 92. The P allele for pea comb and the R allele for rose comb had a frequency of O. 02 and 0.01 respectively, while the recessive forms, rand p alleles for single comb had frequencies of 0.99 and 0.98 respectively. These estimated frequencies were found to be significantly different from the expected ratio based on simple Mendelian mode of inheritance of these traits.